Pelatihan Atlet Bulu Tangkis Koni Kota Mataram - Soemardiawan Soemardiawan; Susi Yundarwati; Fitri Anggraini (Sasambo: Jurnal Abdimas (Journal of Community Service), 2022)
Tujuan Kegitan Kemitraan Masyarakat (PKM) ini adalah utuk melatih kondisi fisik atlit bulu tangkis Koni kota Mataram. PKM dilaksanakan di Koni Kota Mataram dengan Mitra Atlet Bulu tangkis yang berjumlah berjumlah 12 atlet yang sudah di verivikasi oleh KONI Kota Mataram. Metode yangg digunakan adalah pendekatan terpadu melalui implemetasi pendamping pelatihan yang sesuai dengan siklus kegiatan pelatihan yang terstandar, yang meliputi analisis kebutuhan pelatihan, perencanaan pelatihan, penyusunan bahan pelatihan, pelaksanaan pelatihan, dan evaluasi pelatihan. Adapun pelaksaan kegitan dengan tahapan-tahapan sebagai berikut; 1) Sosialisasi atau pemaparan materi 2) peyusunan materi Pendamping Pelatihan peyusunan tes kondisi fisik, 3) pendampingan dalam mengimplementasikan Pelatihan, 4) Evaluasi dan analisis Pelatihan peyusunan instrumen tes serta pengukuran kegiatan. Hasil Pendampingan pelatihan antara lain; 1)  kondisi fisik atlet bulu tangkis KONI Kota Mataram, sebagai bahan rujukan dalam sehingga dapat merumuskan program latihan untuk meningkatkan prestasi atlet, dan 2) peningkatan pemahaman dan keterampilan tentang melaksanakan latihan fisik, Teknik, taktik, psikologisnya. Rekomendasi Diharapkan dari hasil pelatihan yang telah didapatkan oleh atlet dapat di mengaplikasikan pada proses latihan untuk merumuskan program latihan. Sehingga atlet juga harus meningkatkan keterampilan  secara terus menerus, sebagai wujud dari profesionalismenya seorang atlet. Dengan adanya Pendampingan pelatihan kondisi fisik atlet bulu tangkis Koni Kota Mataram dapat teratasi oleh kegiatan pendampingan pelatihan sehingga memberikan dampak positif untuk meningkatkan prestasi atlet KONI Kota Mataram secara terprogram dan sistematis. Mataram City Koni Badminton Athlete Training The purpose of this Community Partnership Activity (PKM) is to train the physical condition of the Koni badminton athletes in the city of Mataram. PKM was held at Koni Mataram City with Badminton Athlete Partners totaling 12 athletes who had been verified by KONI Mataram City. The method used is an integrated approach through the implementation of training assistants in accordance with a standardized training activity cycle, which includes training needs analysis, training planning, preparation of training materials, training implementation, and training evaluation. The implementation of activities with the following stages; 1) Dissemination or presentation of materials 2) Compilation of materials for Training Facilitators in the preparation of physical condition tests, 3) Assistance in implementing training, 4) Evaluation and analysis of training in the preparation of test instruments and measurement of activities. The results of the training assistance include; 1) the physical condition of the KONI badminton athletes in Mataram City, as reference material so that they can formulate training programs to improve athlete performance, and 2) increase understanding and skills in carrying out physical, technical, tactical, psychological exercises. Recommendations It is hoped that the results of the training that have been obtained by athletes can be applied to the training process to formulate an exercise program. So athletes also have to improve skills continuously, as a manifestation of the professionalism of an athlete. With training assistance, the physical condition of the Mataram City KONI badminton athletes can be overcome by training mentoring activities so that it has a positive impact on improving the achievements of Mataram City KONI athletes in a programmatic and systematic manner